2019
DOI: 10.1080/02699052.2019.1566832
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the Chinese version of the Coma Recovery Scale-Revised (CRS-R)

Abstract: Primary Objective: This study aims to validate the Chinese version of the Coma Recovery Scale-Revised (CRS-R). Methods: One hundred sixty-nine patients were assessed with both the CRS-R and the Glasgow Coma Scale (GCS), diagnosed as being in unresponsive wakefulness syndrome (UWS, formerly known as vegetative state), minimally conscious state (MCS), or emergence from MCS (EMCS). A subgroup of 50 patients has been assessed twice by the same rater, within 24 h. Patient outcome was documented six months after ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 21 publications
0
35
0
Order By: Relevance
“…In addition, recent studies have shown similar results with a clinical consensus of a 35.3% misdiagnosis rate [23]. To date, several versions of the CRS-R scale have been developed and validated [24][25][26][27][28]; however, due to the influence of patients' awakening or consciousness fluctuations, movement defects, aphasia, and other problems [29][30][31], a single standard CRS-R behavior evaluation still leads to a certain percentage of a misdiagnosis rate. Therefore, a repeated behavior scale evaluation [32] and personalized item selections [33,34] of the neurobehavioral assessment instrument are recommended to be applied to the consciousness evaluations of clinical patients, which have the potential to improve the reliability/validity of a diagnosis.…”
Section: Introductionmentioning
confidence: 67%
See 1 more Smart Citation
“…In addition, recent studies have shown similar results with a clinical consensus of a 35.3% misdiagnosis rate [23]. To date, several versions of the CRS-R scale have been developed and validated [24][25][26][27][28]; however, due to the influence of patients' awakening or consciousness fluctuations, movement defects, aphasia, and other problems [29][30][31], a single standard CRS-R behavior evaluation still leads to a certain percentage of a misdiagnosis rate. Therefore, a repeated behavior scale evaluation [32] and personalized item selections [33,34] of the neurobehavioral assessment instrument are recommended to be applied to the consciousness evaluations of clinical patients, which have the potential to improve the reliability/validity of a diagnosis.…”
Section: Introductionmentioning
confidence: 67%
“…Therefore, it is highly likely that the clinical worker is highly dependent on the patients' bedside behaviors in the patients' daily management and may not be using systematic and standardized behavioral assessment tools to diagnose awareness. In addition, it was found that the Glasgow Coma Scale (GCS) was widely used for almost all patients admitted to the hospital, and a previous study also showed that the scale was not appropriate for assessing a patient's level of consciousness [24]. Different from the GCS scale, the CRS-R scale has very clear MCS diagnostic criteria, and the evaluation consciousness from various angles can be used to diagnose the consciousness level of patients more sensitively, which greatly reduces the misdiagnosis of patients with prolonged DOC.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, recent studies have shown similar results with a clinical consensus of a 35.3% misdiagnosis rate [20]. To date, several versions of the CRS-R scale have been developed and validated [21][22][23][24][25]; however, due to the influence of patients' awakening or consciousness fluctuations, movement defects, aphasia, and other problems [26][27][28], a single standard CRS-R behavior evaluation still leads to a certain percentage of a misdiagnosis rate. Therefore, a repeated behavior scale evaluation [29] and personalized item selections [30,31] of the neurobehavioral assessment instrument are recommended to be applied to the consciousness evaluations of clinical patients, which have the potential to improve the reliability/validity of a diagnosis.…”
Section: Introductionmentioning
confidence: 68%
“…Therefore, it is highly likely that the clinical worker is highly dependent on the patients' bedside behaviors in the patients' daily management and may not be using systematic and standardized behavioral assessment tools to diagnose awareness. In addition, it was found that the Glasgow Coma Scale (GCS)was widely used for almost all patients admitted to the hospital, and a previous study also showed that the scale was not appropriate for assessing a patient's level of consciousness [21]. Different from the GCS scale, the CRS-R scale has very clear MCS diagnostic criteria, and the evaluation consciousness from various angles can be used to diagnose the consciousness level of patients more sensitively, which greatly reduces the misdiagnosis of patients with prolonged DOC.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, recent studies have shown similar results, with a misdiagnosis rate of 35.3% for clinical consensus [22]. To date, several versions of the CRS-R scale have been developed and validated [23][24][25][26][27]; however, due to the in uence of patients' awakening or consciousness uctuations, movement defects, aphasia, and other problems [28][29][30], a single standard CRS-R behavior evaluation still leads to a nonzero rate of misdiagnosis. Therefore, repeated behavior scale evaluations [31] and personalized item selection [32,33] of the neurobehavioralassessment instrument have been for consciousness evaluations of clinical patients in order to improve the reliability of diagnosis.…”
Section: Introductionmentioning
confidence: 91%